Modul Pembelajaran Multimodal Berbasis Teknologi Augmented Reality untuk Meningkatkan Literasi Informasi dan Digital Siswa - Talitha, Stella; Mulyati, Yeti; Yulianeta, Yulianeta; Kurniawan, Khaerudin (Jurnal Sosioteknologi, 2025)
This study investigates the multimodal representation in the Grade 10 Bahasa Indonesia textbook published under the Kurikulum Merdeka, focusing on how various semiotic modes verbal, visual, typographic, layout, and color are functionally integrated to support meaning-making and student comprehension. Employing a qualitative content analysis method, data were collected through document analysis and analyzed using a multimodal categorization instrument. This instrument classified modes by type, communicative function, and modal integration. The analysis involved identifying modes on selected pages, evaluating the communicative function of each mode, and interpreting the relationships among modes, categorized as complementary, redundant, dominant, or incoherent, to assess cohesion and pedagogical relevance. The results show that visual modes are the most dominant, with typographic and layout features providing emphasis and structural clarity. Complementary relations were most frequent, demonstrating a high degree of synergy between modes in conveying meaning. Instances of redundancy, dominance, or incoherence were minimal but signal areas for improvement. The study concludes that the textbook reflects a pedagogical shift toward multimodal literacy aligned with 21st-century competencies. Practically, the findings inform educators and textbook designers on how to optimize visual-verbal coordination, design layout more coherently, and utilize typography and color meaningfully to foster more inclusive, engaging, and effective language instruction.